Perioperative blood transfusion in radical cystectomy: Analysis of the National Surgical Quality Improvement Program database. (11th July 2016) - Sui, Wilson; Onyeji, Ifeanyi C; Matulay, Justin T; James, Maxwell B; Theofanides, Marissa C; Wenske, Sven; DeCastro, Guarionex J
Abstract : Objectives: To determine whether perioperative blood transfusion is associated with worse 30‐day postoperative outcomes in radical cystectomy patients. Methods: Utilizing the National Surgical Quality Improvement Program database, we identified 2934 patients diagnosed with bladder cancer (International Classification of Diseases Ninth Revision codes 188–188.9) who underwent radical cystectomy (Current Procedure Terminology codes 51570, 51575, 51580, 51585, 51590, 51595, 51596) between 2005 and 2013. Patients were stratified by transfusion status and assessed based on four composite postoperative outcomes: morbidity, surgical site infection, mortality and readmission. Multivariate regression models were used to determine significant independent predictors of the composite outcomes. Results: Overall, 40.1% of patients received a transfusion, and there were significant differences in baseline variables such as age, sex, body mass index, smoking history and comorbidities. Transfusion was associated with increased morbidity, surgical site infection, readmission, operative time and length of stay on unadjusted analyses. On multivariate regression, transfusion was associated with increased morbidity (OR 1.361, 95% CI 1.131–1.638) and surgical site infection (OR 1.371, 95% CI 1.070–1.757). Conclusions: Perioperative blood transfusion is associated with increased risk of postoperative infection and morbidity. Previous work in this area has focused on negative long‐term oncological outcomes, but this is the first study to examine short‐term postoperative outcomes. Future research should focus on the immunosuppressive mechanism of perioperative blood transfusion and on restrictive transfusion guidelines for oncology patients.